Description of Tottonophyes enigmatica gen. nov., sp. nov. (Hydrozoa, Siphonophora, Calycophorae), with a reappraisal of the function and homology of nectophoral canals - Pugh, P. R.; Dunn, C.w.; Haddock, S.h.d. (Zootaxa, 2018)
A new species of calycophoran siphonophore, Tottonophyes enigmatica gen. nov, sp. nov., is described. It has a unique combination of traits, some shared with prayomorphs (including two rounded nectophores) and some with clausophyid diphyomorphs (the nectophores are dissimilar, with one slightly larger and slightly to the anterior of the other, and both possess a somatocyst). Molecular phylogenetic analyses indicate that the new species is the sister group to all other diphyomorphs. A new family, Tottonophyidae, is established for it. Its phylogenetic position and distinct morphology help clarify diphyomorph evolution. The function and homology of the nectophoral canals and somatocyst is also re-examined and further clarification is given to their nomenclature.